2020
DOI: 10.20546/ijcmas.2020.907.097
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Succession and Population Dynamics of Sap Feeders as Influenced by Weather on Sesame

Abstract: Population dynamics of sucking pests of sesame viz. thrips, whitefly, leaf hoppers and aphids were studied. Correlation between the pest population and weather parameters was analyzed and regression equations were developed. Incidence of aphids, leaf hoppers and thrips on sesame crop during kharif season has started on 25 th SMW. Thrips (7.3/ plant) attained peak in the 30 st SMW, whereas, whitefly population reached peak during 27 th SMW with population of 1.7/ plant, whereas, leaf hopper (2.8/plant) and aphi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 2 publications
3
0
0
Order By: Relevance
“…According to Yadav et al [8] the "leafhopper population had negative non significant correlation with temperature and positive correlation with relative humidity and total rainfall the findings are in close akin with present findings". Similar work was made by Mer et al [11] and Saritha et al [17]. Ahir et al [12] reported that "the jassid population had negative correlation with temperature, whereas relative humidity and rainfall were found non significant and positive which is partially corroborates with present findings".…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…According to Yadav et al [8] the "leafhopper population had negative non significant correlation with temperature and positive correlation with relative humidity and total rainfall the findings are in close akin with present findings". Similar work was made by Mer et al [11] and Saritha et al [17]. Ahir et al [12] reported that "the jassid population had negative correlation with temperature, whereas relative humidity and rainfall were found non significant and positive which is partially corroborates with present findings".…”
Section: Resultssupporting
confidence: 92%
“…Nayak et al [15] found that "thrips appeared during 33 rd standard meteorological week and reached to peak (3.84/ top bud leaves) in the second week of September which is close agreement with present results". Saritha et al [17] reported that "the incidence of thrips has started on 27 th SMW and attained peak in the 31 st SMW (3.5 thrips/ plant) which is partially conformity with present findings". Yadav et al [8] reported that "the correlation between thrips and temperature was negative but with relative humidity and total rainfall, the correlation was positive and non significant".…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Even during slight increases, their populations remained insignificant compared to other insects, maintaining minimal activity across the growth season. These findings were partially in accordance with Saritha et al (2020), Ahir et al (2017), Nayak et al (2019), Kandakoor et al (2012) and Priyanka et al (2022). But, the results of this study were found opposing the findings of Shakya et al (2021).…”
Section: Resultssupporting
confidence: 87%
“…The population data for sesame leaf hoppers was recorded at three plant canopy levels viz., lower, middle, and top leaves. Ten plants were selected randomly per spot from five random spots in the plot and data on leafhopper population were collected and the mean population was calculated [3].…”
Section: Methodsmentioning
confidence: 99%